(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: This study aims to describe the implementation results of new medical techniques at An Binh Hospital from 2020 to 2023, and analyze the advantages and challenges encountered during the process. Methods: A cross-sectional study combining both quantitative and qualitative approaches was conducted. Quantitative data were obtained from medical records of 6,979 patients and technical reports. Qualitative data were collected through in-depth interviews and focus group discussions with 18 healthcare staff members. Results: An Binh Hospital introduced 95 new techniques, treating 6,979 patients. The new techniques reduced the average hospital stay from 10 to 6 days, with recovery rates ranging from 94% to 99%. However, the implementation faced challenges, including complex approval procedures, a lack of specialized staff, and insufficient medical equipment. Conclusion: The implementation of new techniques at An Binh Hospital was highly effective but faced several challenges. Streamlining approval processes, improving workforce training, and upgrading medical equipment are essential for optimizing the implementation process.